Ocular alkali lesions in dogs: acetylcysteine and blood serum effects - Campos, Carla Freitas; Jorge, Adriana Torrecilhas; Talieri, Ivia Carmen; Vicenti, Felipe Antônio Mendes; Toledo-Piza, Evandro de; Laus, José Luiz (Brazilian Journal of Veterinary Research and Animal Science, 2003)
Ophthalmic lesions induced by contact with Sodium hydroxide (NaOH) at 3 M concentration in 42 dogs, divided into three groups (G1, G2 and G3), respectively treated with autogenous blood serum, acetylcysteine and a balanced saline solution were investigated. Comparison of the three groups in terms of clinical and microscopical findings showed no significant differences between groups.